Cross-lagged relations between smartphone addiction and flourishing in adolescents - Okur, Sinan; Engin, Mustafa cagri; Kutuk, Hasan; Satici, Seydi Ahmet (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Smartphone addiction has caused serious damage to the psychological health of adolescents. The aim of this longitudinal study was to clearly demonstrate the relationship between smartphone addiction and flourishing in adolescents. A total of 212 Turkish adolescents ( M age = 16.13, age range = 13-17) participated in the study at three time points, three months apart. Findings based on a cross-lagged panel model demonstrated that low levels of flourishing at Time 1 increased adolescents' smartphone addiction levels at Time 2. The results also revealed that smartphone addiction (Time 2) influenced flourishing (Time 3). These findings imply that a low level of flourishing increases smartphone addiction over time, and an increase in the level of smartphone addiction makes adolescents decrease their level of flourishing over time. The current findings offer important implications for mental health researchers and practitioners regarding the relationship between adolescents' smartphone addiction and flourishing level. Based on these implications, effective coping strategies and psycho-educational programs should be developed and implemented that can help increase flourishing and reduce the negative effects of smartphone addiction in adolescents.
Keywords: Smartphone addiction; Flourishing; Mental health; Cross-lagged relations; Adolescents; STUDENTS; Psychology